PERCEPTION OF SABAH LOCAL YOUTHS ON SOCIO âECONOMIC PROSPECT TOWARDS CAREER IN OIL PALM PLANTATION - A., Mohammad Amizi; Abdullah, Norehan; Ali, Jamal (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2017)
Sabah is the biggest state in contributing to the oil palm commodity in Malaysia with 1.54 million hectares of oil palm plantation and contributing 27.4 % of the total oil palm area in Malaysia. The potential and the opportunity of vacancy in this sector were very wide for local people in Sabah especially for the local youth. However the local youth in this state prefer to work in urban area especially most of them migrate to West Malaysia which offered more jobs in manufacturing and services sectors Due to this reason the more than 78 % of labour in this sectors mainly were foreign labour. The rising social issues of the illegal foreign workers and influx of the foreign workers without work permit work in Sabah. In addition another problem arises when the local youth migrate back to Sabah without job due to high of cost of leaving in urban area. This resulted social problem among the youth due to unemployment issue. This study was done in order to analyse the pull or push factors in constructing a particular pattern of perception among the selected respondents on socio economic prospect toward career in oil plantation. A survey method through structured questionnaire was used to collect data from 156 of local youth between 16 to 40 years of age as focused respondents which were selected using random sampling method. Descriptive statistic was applied in order to rank the factors according to demographic factors that affecting the factor of perception of local youth on socio- economic prospect towards career in oil palm plantation.